Raman and FT-IR spectroscopy of prefiring paintings and slips in pre-Hispanic South American pottery—the case of Diaguita Inca pottery: an initial glazing-painting process? (Tinogasta, Catamarca, Argentina) - de la Fuente, Guillermo Adrian; Marte, Fernando Daniel; Mastrangelo, Noemi Elisa; Martínez Carricondo, Marina; Rozas, Guillermo; Vera, Sergio David; Nazar, Carlos Domingo; Tascon, Marcos (Springer, 2021)
Fil: de la Fuente, Guillermo Adrian. Universidad Nacional de Catamarca; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Investigaciones y Transferencia de Catamarca. Universidad Nacional de Catamarca. Centro de Investigaciones y Transferencia de Catamarca; Argentina